Hubungan Indeks Massa Tubuh dan Aktivitas Fisik dengan Performa Akademik Mahasiswa Selama Pandemi Covid-19 - Hamisah Hamisah; Yery Mustari; Putri Indah Sari Chaerul (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Academic performance in students is very important to be studied because there are things that trigger the success of academic performance in students. During the Covid-19 pandemic, the problem of decreasing levels of physical activity that triggers weight gain is prone to occur, this can affect student academic performance. Objective: Knowing the relationship between body mass index and physical activity with student academic performance during the covid-19 pandemic. Methods: Body mass index was obtained from measurements using a scale and microsize. Physical activity using a back index questionnaire. Block writing test scores are used as an indicator for assessing academic performance. Results: This study showed that there was no relationship between body mass index and academic performance. This study also showed that there was no relationship between physical activity and academic performance. Conclusion: The distribution of body mass index in students is dominated by students with normal BMI, for physical activity students are dominated by students with moderate physical activity, for the level of academic performance is dominated by students who have low grades. In this study, there was no correlation between body mass index and academic performance in students, while there was also no correlation between physical activity and academic performance in students